Dynamic Mechanical Response, Cracking Behavior, and Stress Intensity Factors of Cement Mortar Specimens with Open and Closed Flaws - Qizhi Wang; Fangshi Shi; Xiao Wang; Qingling Meng; Xing Li; Jinbo Song; Chang-yi Yu (Shock and Vibration, 2022)
Major civil and military infrastructures are usually located in mountainous areas with complex geological structures. When subjected to impact loads caused by operational blasting or seismic activities, the inherent flaws or joints in the hosting rock mass may grow irreversibly and eventually and cause the entire structure to collapse. It is, therefore, desirable to understand the mechanical and cracking behaviors of flawed rock structures under dynamic loads. In this work, the cement mortar is used to make the plate specimens, and two different types of flaws, i.e., the open and the closed (resin-filled) flaws, with different inclination angles from 0° to 90° with respect to the loading direction are prefabricated. The nominal strength, crack initiation, and failure characteristics of the specimens under different loading rates are investigated using the split Hopkinson bar (SHPB) system in conjunction with the digital image correlation (DIC) technique. The results indicate that the dynamic nominal strength of both two types of specimens shows similar loading rate and flaw angle dependency, specifically, monotonically increasing with the increase of the loading rate while increasing first and then decreasing with increasing the flaw inclination angle. The strength of specimens with an open flaw is obviously lower than that of the specimens with a closed flaw at a similar loading rate. Besides, the failure mode of specimens with an open flaw is mainly an X-shaped tensile or tensile-shear mixed form regardless of the flaw inclination, whereas the resin-filled flawed specimens always fail in the form of an atypical X-shaped shear pattern with obvious randomness. Moreover, the stress field around the crack tip is carefully extracted based on the obtained displacement field from DIC analysis; the stress intensity factors at crack initiation onset also show flaw inclination- and loading rate-dependent behavior. The strength, cracking behavior, and stress field around the tip during the dynamic loading are closely related to the friction effect between the flaw surfaces. The findings in this work provide some basic insights into the cracking mechanism of rock with open and closed flaws under dynamic loading conditions.